SOLID STATE TRANSFORMER (SST) AND THE CHALLENGES OF THE FUTURE GRID - Kadandani, Nasiru B.; Hassan, Sahalu; Abubakar, Isiyaku (FUDMA Journal of Sciences, 2023)
Power flow management in both transmission and distribution grid networks is continuously being challenged by increased integration of distributed generations that are stochastic and intermittent in nature. This paper investigates the anticipated roles or functionalities required from solid state transformer (SST) to enable it address the challenges faced by the grid network. The SST is a power electronics based transformer build with flexibilities and intelligence required for performing ancillary services to the grid. The paper shows that, with the aid of SST, smooth integration of renewable energy sources and other functionalities such as power factor correction, reactive power compensation, harmonics mitigation, fault ride through and or fault isolation can be achieved in the future grid.